Child Development and Nutritional Status of Children Under Five: A Cross-Sectional Study of a Fishermen Community in Terengganu, Malaysia - Bahtiar, Badriah Aisyah; Ali, Asma'; Yusof, Hayati Mohd; Kamarudin, Khairil Shazmin (Jurnal Gizi dan Pangan, 2021)
This study aims to determine child development, nutritional status and the association between child development and nutritional status. This cross-sectional study was conducted among 60 fishermen’s children under five years old in selected districts in Terengganu. All respondents were assisted by their mothers during the assessment. Child development was evaluated through the Denver II Development Screening Test. Nutritional status was determined via the anthropometry assessment (BMI-for-age and height-for-age). Preponderantly, the prevalence of suspected development delay of children under-five in Terengganu was 31.7%. The prevalence of suspected delay for language, fine motor-adaptive, and personal-social skills were 15.0%, 1.7%, and 16.7%, respectively. BMI-for-age z-score and height for age z-score of these children were -1.62±1.23 and -0.27±1.41, respectively, indicating a normal range; nonetheless, there were still children that were wasted (23.3%), severely wasted (13.3%), stunted (5.0%), severely stunted (1.7%), and at risk of being overweight (1.7%). However, the chi square test showed there was no association found between child development and nutritional status, BMI-for-age and height-for-age (p>0.001), among fishermen’s children under-five in this study. The nutritional status had no effect on the development of these fishermen's children, but may have been influenced by other factors such as stimulating surroundings, parenting abilities, and culture.